PENDEKATAN BISNIS BUMDES BERKEMAJUAN DI KONDISI WABAH PANDEMI COVID’19 - Hadi Ismanto Ismanto; Muhammad Zainuddin Fathoni; Vembri Aulia Rahmi (Universitas Muhammadiyah Gresik, 2020)
The impact of the Covid'19 pandemic outbreak rocked almost more than half of the world economy. In fact, many large world-class companies have suffered losses. This study seeks to describe the survival capacity of village economic institutions in supporting the economic welfare of small entrepreneurs during the pandemic that hit the country. Qualitative descriptive is used as the method of this research. The results of the study explain that BUMDes are able to survive in running the economy during a pandemic through certain business approaches, such as: changing the marketing method for village products, designing new business strategies, arousing entrepreneurial spirit, and improving service quality. Thus it can be concluded that BUMDes was able to anticipate problems in business management during the Covid'19 pandemic